2014
DOI: 10.2147/jpr.s37589
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation for neuropathic pain: current perspectives

Abstract: Neuropathic pain constitutes a significant portion of chronic pain. Patients with neuropathic pain are usually more heavily burdened than patients with nociceptive pain. They suffer more often from insomnia, anxiety, and depression. Moreover, analgesic medication often has an insufficient effect on neuropathic pain. Spinal cord stimulation constitutes a therapy alternative that, to date, remains underused. In the last 10 to 15 years, it has undergone constant technical advancement. This review gives an overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 120 publications
2
74
1
3
Order By: Relevance
“…Spinal cord stimulation is contraindicated in the presence of marked psychological difficulties (major depression, anxiety, personality disorder, psychosis or poor coping strategy), coagulation abnormalities (including anticoagulant therapy), demand pacemaker, implanted defibrillator, systemic/ local infection and immunosuppression (3,23). …”
Section: Indications For Usementioning
confidence: 99%
“…Spinal cord stimulation is contraindicated in the presence of marked psychological difficulties (major depression, anxiety, personality disorder, psychosis or poor coping strategy), coagulation abnormalities (including anticoagulant therapy), demand pacemaker, implanted defibrillator, systemic/ local infection and immunosuppression (3,23). …”
Section: Indications For Usementioning
confidence: 99%
“…Finan and Smith (2014) found in review of studies exploring the relationship between depression, insomnia and CP found that the existence of insomnia and depression resulted in increased pain severity (p. 176). Untreated or undertreated depression in chronic pain sufferers has been linked to poor medical and surgical outcome (Finan and Smith 2014;Wolter 2014). Appropriate treatment of depression in chronic pain is not only essential for reducing the pain experience but for helping the patient with motivation to engage in a self-management regimen.…”
Section: Post Morbid Functioningmentioning
confidence: 99%
“…At present, a variety of implantable nerve stimulators have been clinically employed and demonstrated to be efficacious in alleviating numerous pathologies. Several implantable devices are already in routine use, including hypoglossal nerve stimulation in patients with severe obstructive sleep apnea [76,137]; chronic spinal cord stimulation in patients with severe neuropathic pain [153,160]; direct electrical stimulation of peripheral nerves in patients with bladder, bowel, and sexual dysfunction [30,40]; and even transcutaneous stimulation of the trigeminal nerve in migraine patients [35,36,75,107,125,136,142]. Deep brain stimulation (DBS) is arguably the most successful example of a bioelectric technology that has transitioned into the clinical realm to treat a variety of neurological disorders with an incredible degree of efficacy [59,108].…”
Section: Introductionmentioning
confidence: 99%